2022
DOI: 10.5897/ijps2022.5010
|View full text |Cite
|
Sign up to set email alerts
|

Uncooled PV cell under variable light concentration: Determination of profiles of the temperature, the intrinsic properties and the carrier density

Abstract: Studies on concentrated light influence do not take into account the effect of the heating and this proves to be harmful on photovoltaic parameters. The main purpose of this work is to study the effects of light concentration and the heating caused by this concentration on intrinsic properties and carrier density profile. A thermal model of the PV cell is proposed. By applying the power balance at the steady-state, the PV cell thermal equation is determined. The resolution of this equation leads to temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 24 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…This has been proved by Savadogo et al [7] who have shown a decrease of electron and hole mobility and diffusion coefficients with temperature rise. These authors also showed that temperature rise leads to a decrease in gap energy.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…This has been proved by Savadogo et al [7] who have shown a decrease of electron and hole mobility and diffusion coefficients with temperature rise. These authors also showed that temperature rise leads to a decrease in gap energy.…”
Section: Introductionmentioning
confidence: 63%
“…In the equations 11 and 12, τ represents the excess minority carriers (electrons) lifetime. µn,p(T) and Dn,p(T) respectively represent the mobility and diffusion coefficients of electrons and holes versus temperature [7]. It thus emerges that the diffusion coefficient and the diffusion length in the base of PV cell of the present model, respectively D c (T) and L c (T) depend on the temperature.…”
Section: The Diffusion Parametersmentioning
confidence: 78%
See 3 more Smart Citations